Corrosion behavior of superhydrophobic surfaces: A review - Adel M.A. Mohamed; Aboubakr M. Abdullah; Nathalie A. Younan (Arabian Journal of Chemistry, 2015)
Superhydrophobic surfaces have evoked great interest in researchers for both purely academic pursuits and industrial applications. Metal corrosion is a serious problem, both economically and operationally, for engineering systems such as aircraft, automobiles, pipelines, and naval vessels. Due to the broad range of potential applications of superhydrophobic surfaces, there is a need for a deeper understanding of not only how to fabricate such surfaces using simple methods, but also how specific surface properties, such as morphology, roughness, and surface chemistry, affect surface wetting and stability. In this article, a comprehensive review is presented on the researches and developments related to superhydrophobicity phenomena, fabrication of superhydrophobic surface and applications. A significant attention is paid to state of the art on corrosion performance of superhydrophobic coatings.